ANALISIS KESUKSESAN PADA APLIKASI TRANSPORTASI ONLINE DARI PERSPEKTIF PENGGUNA - Willy Willy; Amrizal Amrizal (Universitas Putera Batam, 2025)
This study aims to measure the success of the Go-Jek application from a user perspective using the Information System Success Model (ISSM) by DeLone & McLean. Go-Jek, as a pioneer of online transportation in Indonesia since 2010, offers various features that simplify people's daily activities. Using the ISSM approach, this study evaluates six main factors: information quality, system quality, service quality, usage intention, user satisfaction, and net benefits. Data were collected through questionnaires distributed to 100 respondents in Batam City and Tanjungpinang. The analysis results show that information quality, system, and service have a significant influence on user satisfaction. Users feel helped by the ease of application, simple language, and responsive service offered by Go-Jek. In addition, user satisfaction is shown to be a key determinant of reuse intentions, which directly affects the net benefits for users and the company. Go-Jek's success is also supported by continuous innovation in improving user experience. This research provides important insights for PT Go-Jek in developing better technology-based services, while contributing to the literature related to information systems evaluation. This research confirms that the quality of information, systems, and services are key factors that must be continuously improved to maintain user satisfaction and loyalty.